(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Mammalian bombesin (Bn) receptors comprise 3 subtypes: BB1, BB2, BB3 (nomenclature recommended by the NC-IUPHAR Subcommittee on bombesin receptors, [118, 5]). BB1 and BB2 are activated by the endogenous ligands neuromedin B (NMB), gastrin-releasing peptide (GRP), and GRP-(18-27). bombesin is a tetra-decapeptide, originally derived from amphibians and structurally closely related to GRP. The three Bn receptor subtypes couple primarily to the Gq/11 and G12/13 family of G proteins [118]. Each of these receptors is widely distributed in the CNS and peripheral tissues [81, 118, 259, 288, 373, 115, 6, 375, 125, 204]. Activation of BB1 and BB2 receptors causes a wide range of physiological/pathophysiogical actions, including the stimulation of normal and neoplastic tissue growth, smooth-muscle contraction, respiration, gastrointestinal motility, feeding behavior, secretion and many central nervous system effects including regulation of circadian rhythm, body temperature control, sighing, behavioral disorders and mediation of pruritus [210, 118, 204, 259, 211, 37, 375, 211, 44, 4]. BB3 is an orphan receptor, although some propose it is constitutively active [328]. BB3 receptor knockout studies show it has important roles in glucose and insulin regulation, metabolic homeostasis, feeding, regulation of body temperature, obesity, diabetes mellitus and growth of normal/neoplastic tissues [154, 81, 223, 208, 4, 208]. Bn receptors are one of the most frequently overexpressed receptors in cancers and are receiving increased attention for their roles in tumor growth, as well as for tumour imaging and for receptor-targeted cytotoxicity especially for advanced prostate and breast cancer [210, 167, 13, 136, 377, 371]. Bn receptors are also receiving attention because they are one of the primary neurotransmitters for pruritus [37, 128, 240].